ANALISIS STABILITAS SISTEM FONDASI HYDROPOWER PLANT PADA SUNGAI BAWAH TANAH ZONA KARST - , Sulha ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Topographically and geologically, Gunung Kidul Regency is a mountainous karst and has very deep aquifers and groundwater. The soil condition is hard to absorb and store water, this condition makes people hard to fulfill their fresh water need. This area has a big water resource potential, especially in Goa Seropan, in this area, the water resource comes out the underground river. Goa Seropan water resource is utilized not only to fulfill the daily needs but also to run the turbine. Turbine produces electrical energy to absorb water. Determining both location and construction type of hydropower plant's foundation is a solution of the water resource problems in this area. This research is aimed at analysis of rock engineering properties and foundation system stability. In this study, an analysis using the element method up to model plan strains with the help of PLAXIS Software v 8.2. The approach of analysis is done on the Foundation look by using the 4 model geometry. Variations in the dimensions of the model geometry of horizontal plates namely 0.40 meters and 0.45 meters. Vertical walls, i.e. 0.30 meters and 0.35 meters, and bored pile i.e. 0.20 meters, 0.25 m and 0.30 meters. Material properties in the construction site are drawn from the results of research and test laboratory of IWRM Goa Seropan technical team and the University of Gadjah Mada. Input data from field measurements geometry simplified, whereas input parameters of soil, rock and concrete from secondary data. Model analyses of the static and dynamic loads using the PLAXIS Software v 8.2 are validated based on the manual calculations. Results of the numerical simulation showed that the addition of bored pile for 0.20 meter on foundation system hydropower plants able for resisting stresses occur in the land base as a result of the earthquake loads by a factor of safety of 2.01. The Foundation system in accordance with the model geometry I with horizontal plate dimensions = 0.40 m, vertical wall = 0.30 m, and bored pile = 0.20 m is safety enough and stable toward static or dynamic load. The difference in displacement vertical maximum two point of foundations according to the geometry model of I. from all of loads will cause angular distortion for 0,2159 cm or 1/1112 is still relatively small angular distortion of permission i.e. 1/750. Maximum horizontal distortion foundations and buildings due to earthquake loads 355, 4 g for 0,379% is still relatively safe if itâs reviewed against allowable distortion amounting to 1.54%. PLAXIS Software proved to be able to model the wall behaviour of cave and structure of which bearing the burden of a static and dynamic quite well.